The Prevalence of Crohn’s Disease in the Israeli Kibbutz Population - Yaron Niv (Canadian Journal of Gastroenterology)
An epidemiological study of Crohn’s disease was performed in 279 Israeli Kibbutzim (rural communities) (population 121,403). The prevalence on December 31, 1987 was 25.53 per 100,000 population. When the data were stratified according to ethnic group, the highest point prevalence was found in Asian/African-born Jews (41.76 per 100,000 population), greater than in Israeli-born, or European/American-born Kibbutz members (38.92 and 17.35 cases per 100,000 population, respectively). There were 15 women and 16 men (female to male ratio 0.94). The average age of patients was 45 years in the survey year, and 35 years at diagnosis. Terminal ileitis was found in 69%, ileocolitis in 19%, and colitis in 12%. Probable complications of Crohn’s disease were observed in 10 cases (32%). Anemia was demonstrated in two cases (6%). The high rate of Crohn’s disease prevalence among Israeli-born versus European/American-born Kibbutz members may point to a role for environmental factors in the etiology of the disease.